Determinan Sosial dan Ekonomi yang Berkontribusi pada Ketahanan Pangan Rumah Tangga di Wilayah Pesisir - Kharis Meiwan K. Telaumbanua (Lembaga Pengembangan Kinerja Dosen, 2025)
Food security is a strategic issue that is directly related to community welfare, especially in coastal areas that are vulnerable to climate change and economic fluctuations. This study aims to identify and analyze social and economic determinants that contribute to the level of household food security in coastal areas. The method used is a quantitative approach with a survey technique of 150 households in three coastal villages. The variables studied include income level, education, access to markets, social participation, and ownership of productive assets. The results of the study indicate that income factors, education of the head of the family, and participation in social groups have a significant influence on household food security. This finding confirms that food security is not only determined by food availability alone, but also by socio-economic factors that shape household resilience in accessing and utilizing food optimally. The implications of this study emphasize the need for multi-sector policy interventions that focus on increasing income, education, and social empowerment to strengthen sustainable food security in coastal areas.